Forty years of experiments on aquatic invasive species: are study biases limiting our understanding of impacts? - Thomsen, Mads; Wernberg, Thomas; Olden, Julian; Byers, James E.; Bruno, John; Silliman, Brian; Schiel, David (NeoBiota, 2014)
Invasions by non-native species are a threat to biodiversity because invaders can impact native populations, communities and entire ecosystems. To manage this threat, it is necessary to have a strong mechanistic understanding of how non-native species affect local species and communities. We reviewed 259 published papers (1972–2012) that described field experiments quantifying the impact of aquatic non-native species, to examine whether various types of study biases are limiting this understanding. Our review revealed that invasion impacts had been experimentally quantified for 101 aquatic non-native species, in all major freshwater and marine habitats, on all continents except Antarctica and for most higher taxonomic groupings. Over one-quarter (26%) of studies included tests for impacts on local biodiversity. However, despite this extensive research effort, certain taxa, habitats and regions remain poorly studied. For example, of the over one hundred species examined in previous studies, only one was a marine fish and only six were herbivores. Furthermore, over half (53%) the studies were from the USA and two-thirds (66%) were from experiments conducted in temperate latitudes. By contrast, only 3% of studies were from Africa and <2% from high latitudes. We also found that one-fifth (20%) of studies were conducted in estuaries, but only 1% from coral reefs. Finally, we note that the standard procedure of pooling or not reporting non-significant treatments and responses is likely to limit future synthetic advancement by biasing meta-analysis and severely limiting our ability to identify non-native species with none or negligible ecological impacts. In conclusion, a future focus on poorly-studied taxa, habitats and regions, and enhanced reporting of results, should improve our understanding and management of impacts associated with aquatic non-native species.